Burden of hospitalizations and outpatient visits associated with moderate and severe acute graft-versus-host disease in Finland and Sweden: a real-world data study - Sabatelli Lorenzo; Keränen Mikko; Viayna Elisabet; Roset Montserrat; Lara Nuria; Thunström Daniel; Pfeiffer Minja; Nicklasson Malin; Itälä-Remes Maija (SPRINGER, 2022)
Purpose
The aim of this study was to describe patient characteristics and quantify hospital stays and outpatient visits (H&OV) following diagnosis with moderate-to-severe acute graft-versus-host disease (aGVHD) in Finland and Sweden.
Methods
A retrospective chart audit collected data from patient medical records of 3 specialized centers performing allogeneic hematopoietic stem cell transplantation (HSCT; Finland, n = 2; Sweden, n = 1). Eligible patients received allogeneic HSCT (January 1, 2016-June 30, 2017) from any donor source, were diagnosed with grade II-IV aGVHD (MAGIC or modified Glucksberg criteria) at any time from transplantation to 12 months before data collection, and were >= 18 years old at diagnosis. Criteria for comparing patients graded with modified Glucksberg and MAGIC severity scales were defined.
Results
Fifty-five patients (Finland, n = 45; Sweden, n = 10) were included. Myeloablative conditioning was the most common conditioning regimen (81.8%); immunosuppression regimens were based on combinations of methotrexate (96.4%), in vivo T-cell depletion (80.0%), cyclosporine (63.6%), mycophenolate (40.0%), and tacrolimus (34.5%). Sixteen patients (29.1%) developed grade III/IV aGVHD; skin was the most common organ involved (80.0%). Most patients required >= 1 hospital stay (89.1%; median of 2 hospitalizations per patient); 7 patients (14.3%) required admission to an intensive care unit. Median hospitalization duration from HSCT to discharge was 26 days. Most patients also required outpatient or emergency department visits (90.9%). Subgroup analyses showed longer hospital stays for patients receiving multiple treatment lines; no clear differences in H&OV were observed between prophylactic regimens.
Conclusion
Based on this retrospective study, moderate-to-severe aGVHD is associated with considerable healthcare resource utilization in Finland and Sweden, particularly in patients who received multiple lines of therapy.